A evolução do comércio dos Estados Brasileiros: uma aplicação do modelo de Heckscher-Ohlin - Nobre, Fábio Chaves (2006)
The objective of this research is to show how the Brazilian states trade their products worldwide. The theoretical framework is based upon the theorem of Heckscher-Ohlin in which a country or region tends to specialize in the production of a good in which the abundant factor of production is more intensively used. this research evaluates to trade patterns of 15 products of the Annual Industrial Research and it was evidenced that great part of the production depends on the factor production human capital. Therefore, the Brazilian states that are abundant on this production factor tends to concentrate its production in the products that use this factor intensively, this way, the sate will be internationaly competitive. In the same way for the work force, therefore the national states that are endowed with this factor in abundance tends to concentrate its production in the products that uses this factor of production intensively.